Cancer mortality in Guarapari, Espiríto Santo State, Brazil, with areas of high natural radioactivity - Rafael Gonçalves Ferreira; Marcio Vinicius de Nardi de Angeli; Debora Rocha Barboza; Gustavo de Paula Batista de Carvalho-Silva; Romildo Rocha Azevedo Junior; Fausto Edmundo Lima Pereira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Guarapari, a municipality of the state of Espírito Santo, Brazil, reported higher mortality rates for the most common cancers from 1996 to 2000. This municipality has beaches with high natural radioactivity. To verify whether this excessive cancer mortality rate still exist in Guarapari, mortality rates for all causes, cancers, and the most prevalent cancers in this municipality were studied from 2000 to 2018 and compared with those observed in the state. Data on all-cause mortality, all-cancer mortality, and mortality from cancer of the esophagus, stomach, larynx, trachea, bronchi and lung, prostate, breast, and leukemias were collected in Brazilian Health Informatics Department (DATASUS) from 2000 to 2018. Mortality rates were calculated by direct method. Standardized age-adjusted rates (SAAR) were calculated based on standard of the World Health Organization (WHO) world population. Crude mortality rates were calculated for each municipality and SAAR for the state and nine municipalities where natural radioactivity was evaluated. Mortality rates from all causes, all cancers, and different cancers observed in Guarapari did not differ significantly from those observed in the state or municipalities with more than 100,000 inhabitants. Radioactivity levels and mortality rates showed no correlation in nine municipalities where natural radioactivity was known. In conclusion, results showed that mortality from cancer and all causes in Guarapari did not differ from those observed in the state and that there was no correlation between the levels of natural radioactivity and mortality from cancer in areas where natural radioactivity was evaluated.